Nigerian dental anxiety, fear, and phobia: A prevalence review - Eseadi, Chiedu; Surjaningrum, Endang R. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Dental anxiety, dental fear, and dental phobia are psychological conditions that commonly affect individuals, making dental visits and treatments daunting and distressing. Purpose: This study aimed to evaluate dental anxiety, fear, and phobia among Nigerians through a literature review design. The main outcome of the study was to assess the prevalence of dental anxiety, fear, and phobia among Nigerians. Methods: The research databases used were Google Scholar, PubMed, PsycINFO, CINAHL, and Cochrane. After independent assessors read the full texts to ensure eligibility, 23 studies were selected for inclusion, while 65 papers were excluded. These studies documented the existence of dental anxiety, fear, and phobia among Nigerians from 2002 to 2022. Results: Among the selected studies, there were 21 dental anxiety studies, one dental fear study, and one dental phobia study. The prevalence of dental anxiety in these studies ranged from 7.43% to 62.8%, the prevalence of dental fear was 36.8%, and the prevalence of dental phobia was 30%. Notably, dental anxiety studies were more frequently carried out among residents of South-Western Nigeria than residents of other regions of the country. The Modified Dental Anxiety Scale was the most commonly used instrument for assessing dental anxiety among study participants. Dental anxiety, fear, and phobia were commonly associated with dental health concerns, past pain experiences, and previous traumatic dental treatment among Nigerians. Conclusions: Dental anxiety, dental fear, and dental phobia affect both Nigerian children, adolescents, and adults, though the prevalence and extent of investigation vary by group and region. Further empirical studies are needed across different regions of the country, particularly in the South-Eastern and North-Eastern regions, focusing on hospitals, schools, and community-based settings. Psychological services can be implemented alongside dental treatments to help alleviate anxiety, fear, and phobias in Nigerian dental patients.